Effects of ultrasonic pretreatment and glycosylation on functional properties of casein grafted with glucose. Issue 5 (28th December 2016) - Bi, Weiwei; Ge, Wei; Li, Xiaodong; Du, Lingling; Zhao, Guixing; Wang, Haixia; Qu, Xiuwei
Abstract: Caseins are the predominant proteins in milk. The Maillard reaction is a non‐enzymatic reaction between reducing sugars and amino acids. This work investigated the impact of ultrasound pretreatment on the Maillard reaction and functional properties of glycated casein. Casein solution was treated with ultrasound for 0, 10, 20, 30, and 40 min prior to Maillard reaction. Results revealed that the absorbance at 294 nm reached maximum after 20 min of ultrasound pretreatment. Moreover, glycated casein obtained by Maillard reaction coupled with 20 min ultrasound pretreatment had the highest water holding capacity 67.81% ± 1.72%, gel strength 165.05 ± 2.72 g, the emulsifying activity index 91.76 m 2 /g, the emulsion stability index 20.67 min, reducing power 0.682 compared with other samples. The results of SEM confirmed microstructure of gel improved. Consequently, ultrasonic pretreatment could improve the efficiency of the reaction. Moreover, ultrasonic pretreatment had certain impact on the functional properties of Maillard reaction products. Practical applications: Casein solution was treated with ultrasonic pretreatment prior to Maillard reaction. Ultrasonic pretreatment can increase the reaction rate of casein and glucose. Ultrasonic pretreatment had improved functional properties of glycated casein. Therefore, it pointed out the usefulness of ultrasound as an effective method of pretreatment to promote the formation of functional ingredients by Maillard reaction.